The use of online database among the Bachelor of Science in Information Studies (hons) (Library and Information Management) (IM220) students in UiTM Kedah / Siti Asma’ Mohd Rozid - Mohd Rozid, Siti Asma’ (Faculty of Information Management, 2012)
This research aims to study the use of online database among BIS students in UiTM Kedah. The study was made in order to know about content, accessibility and interface of online database. The purpose of this study to measure the level of user satisfaction on the content, how they access online database and study whether the interface influence user in accessing the online database or not. The sample consists of 231 respondents from semester 1 until semester 6. Only 144 respondents will be selected as a sample for this study. The data was collected using the questionnaire instrument. This study was use stratified random sampling in order to collect data from respondents. Through the finding that has been generated will improve the existing online database that provided in Sultan Badlishah Library.